General (Czech Journal of International Relations, 1967)
Dozens of friendly and less friendly, scholarly and popular books have been written about the person of General Charles de Gaulle, describing de Gaulle himself and the so-called Gaullism to varying degrees. The inspiration for these books is usually the same as that mentioned by Ján Cierny for his current book General: the modern development of France cannot be imagined without this personality, who is also extremely interesting, complex, contradictory and attractive. However, the book "The General" wants to contribute to the understanding and closer knowledge of this leading personality of today's France and the saintly statesman in its own specific form. The author does not choose the path of a precise chronological description of the development of all events, nor the path of theoretical analysis and generalization.